1996
DOI: 10.1074/jbc.271.32.19563
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Zinc Motif in Sequence Recognition by DNA Primases

Abstract: The DNA primase of bacteriophage T7 has a zinc-binding motif that is essential for the recognition of the sequence 3-CTG-5. The T7 primase also catalyzes helicase activity, a reaction coupled to nucleotide hydrolysis. We have replaced the zinc motif of the T7 primase with those found in the gene 61 primase of phage T4 and the DnaG primase of Escherichia coli. The T4 and E. coli primases recognize the sequences 3-T(C/T)G-5 and 3-GTC-5, respectively. Both chimeric proteins can partially replace T7 primase in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 58 publications
1
55
1
Order By: Relevance
“…The 3Ј-cytidine is required for recognition but is not copied into the primer. Although limited synthesis of pppAA dinucleotide has been observed to occur at the trinucleotide sequence 5Ј-TTC-3Ј under certain conditions, the pppAA dinucleotide is not extended further (6,21). Analysis of the oligoribonucleotide primers attached to the 5Ј-end of Okazaki fragments both in vivo and in vitro has shown that the T7 primase synthesizes predominantly pppAC(C/A)(C/A) tetraribonucleotides; UMP and GMP are not found in the primers (17,18,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 3Ј-cytidine is required for recognition but is not copied into the primer. Although limited synthesis of pppAA dinucleotide has been observed to occur at the trinucleotide sequence 5Ј-TTC-3Ј under certain conditions, the pppAA dinucleotide is not extended further (6,21). Analysis of the oligoribonucleotide primers attached to the 5Ј-end of Okazaki fragments both in vivo and in vitro has shown that the T7 primase synthesizes predominantly pppAC(C/A)(C/A) tetraribonucleotides; UMP and GMP are not found in the primers (17,18,20).…”
mentioning
confidence: 99%
“…Although the zincbinding motif is essential for primer synthesis (5), it alone cannot account for the ability of the protein to recognize specific sequences on ssDNA (6). Gene 4 protein is essential for phage growth and physically interacts with both the gene 5 DNA polymerase and the gene 2.5 ssDNA binding protein to mediate leading and lagging strand synthesis at the T7 replication fork (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…DnaG-type primase structures exhibit zinc-ribbon domains (15,26,27) that are tethered loosely to their catalytic domains and regulate initiation of primer synthesis and length (26)(27)(28)(29). Pri-type primases feature zincknuckle or zinc-stem structures inserted in their PriS-catalytic domain that were suggested to enforce the interaction with the ssDNA template, but were shown not to be essential for primase activity, in contrast to the zinc ribbon domain (18,20).…”
mentioning
confidence: 99%
“…1A for T7 DNA primase) contain six conserved sequence motifs (9). An N-terminal zinc-binding domain (ZBD) formed by motif I is a determinant for recognition of a specific sequence in DNA (10)(11)(12)(13). Motifs II-VI are located in the C-terminal RNA polymerase domain (RPD) that consists of two subdomains (Fig.…”
mentioning
confidence: 99%